DETEKSI SIMULTAN CMV DAN CHIVMV PENYEBAB PENYAKIT MOSAIK PADA TANAMAN CABAI DENGAN DUPLEX RT-PCR - Chandra, I Gede Agus Adi; Nyana, I Dewa Nyoman; Wirya, I G N Alit Susanta; Suastika, Gede (Journal of Agricultural Science and Biotechnology, 2016)
Detect the presence virus causes mosaic symptoms by CMV and ChiVMV infecting chili pepper plants at the same time was conducted. There needs a study that aims to detect the associations of both viruses causes mosaic symptoms by single or double infection and simplify the detection process which is necessary for a long and expensive process. The used method is a duplex RT-PCR in hopes of simultaneously detecting two viruses causes mosaic disease. Based on the results of the study showed that the duplex RT-PCR method can detect double infection of CMV and ChiVMV on chili plants and this method more effective to detect two viruses simultaneously in a single PCR reaction.
Keywords: chili pepper; CMV; ChiVMV; Duplex RT-PCR